A Study of Academic Administration Competency of the Academic Administrators at Schools under Phetchabun Primary Education Service Area Office 3 - Paree, Anucha; Tanya, Somboon; Julsiripong, Sittisak; Kidkarn, Rattakorn (Ratchaphruek Journal, 2014)
The objectives of this research were: 1) to study the academic administrative competences of the academic administrators under the Phetchabun Primary Education Service Area Office 3, and 2) survey the needs for development in academic administrative competences for academic administrators under the Phetchabun Primary Education Service Area Office 3. They was divided into two steps; 1) Study of required academic administration by the experts meeting given the required data in determining of 10 experts in academic administration. The instruments used cameras and videorecording. There were 4 performances of academic management from the Secretariat of the Council and 2) theneeds for development in academic administration competences for academic administrators were surveyed from the population of 227 academic administrators under the Phetchabun Primary Education Service Area Office 3 in the academic year 2011. The samples of 144 administrators were selected by using Krejcie and Morgan Table for districtstratified sampling. The data collection tool was a 5-rating scale questionnaire on the needs of the development of academic administration competences. The data were analyzed by using means (X) and standard deviations (S.D.). The results showed that 1. Competencies needed for academic administration competency for executives of the Phetchabun Primary Education Service Area Office 3 contain17 performances. 2. The developed performance management needed academic administration competency for executives the Phetchabun Primary Education Service Area Office 3contain 9 performances.